Investigation of throughput and packet drop on VANET using NCTUns simulation software / Mohd Afiq Ismail Mansor - Ismail Mansor, Mohd Afiq (2012)
Vehicular Ad-hoc Network (VANET) is a technology that uses moving car as a node in a network to form a mobile network. The purpose of this project is to run V ANET using National Chiao Tung University network simulator (NCTUns) to obtain throughput and packet dropped at each node at different speed. Simulation takes into account of the Manhattan mobility environment, using two ray ground reflections as the propagation model. The investigation of throughput and packet drop was done from 5 up to 25 V ANET nodes using Ad-hoc On-demand Distance Vector (AODV) protocol to evaluate the performance of the nodes.